Interventions for vaginismus. - McGuire, H; Hawton, K (2003)
BACKGROUND: Vaginismus is involuntary vaginal muscle contraction which makes sexual intercourse difficult or impossible. It is one of the more common female psychosexual problems. Various therapeutic strategies for vaginismus, such as sex therapy and desensitization, have been considered in uncontrolled studies. OBJECTIVES: The aim of this review is to determine the clinical effectiveness of treatments for vaginismus and also to examine the role of partner participation in the effectiveness of the treatment. SEARCH STRATEGY: The Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register (Issue 3, 2000), the Cochrane Controlled Trials Register (Cochrane Library, Issue 2, 2002), MEDLINE (1966 to Nov 2002), EMBASE (1980 to Nov 2002), PsycINFO (1967 to Nov 2002) and CINAHL (1982 to Nov 2002) were searched. The Journal of Sex Research (1974 to 1999), Sexual and Marital Therapy (1986 to 1999), Sexual Dysfunction (1998 to 1999) and the Journal of Sex and Marital Therapy (1974 to 1999) were handsearched. Reference lists and conference abstracts were searched. Experts in the field were contacted regarding unpublished material. SELECTION CRITERIA: Controlled trials comparing treatments for vaginismus with another treatment, a placebo treatment, treatment as usual or waiting list control. DATA COLLECTION AND ANALYSIS: The reviewers extracted data which were verified with the trial investigator. MAIN RESULTS: Two controlled trials were identified although data were only available from one trial. The second trial compared two forms of systematic desensitization and reported no discernible differences between them. REVIEWER'S CONCLUSIONS: In spite of encouraging results reported from uncontrolled series of patients there is very limited evidence from controlled trials concerning the effectiveness treatments for vaginismus. Further trials are need to compare therapies with waiting list control and with other therapies.